Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Di Waroeng Steak And Shake Cabang Margonda Depok - Lestari, Nurlaela Eva Puji (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2020)
Service is one of the important factors in carrying out the company's operational activities. Preparing customer service well is the same as making a company succeed in its business. Conversely, ignoring customer service is just making a failure for a company. This study used a quantitative research method using the SPSS version 21 application. The population taken was the number of visitors at Waroeng Steak and Shake margonda as many as 135 visitors. Determination of the number of samples using Slovin formula with an error rate of 5% found the number of respondents was 100 respondents. The sampling method uses non probability sampling with incidental sampling techniques. The instrument of this study uses a questionnaire with the number of questions as many as 30 questions and analysis used, namely the correlation test, determination test and regression test. The results of the study show that there is a very strong influence between the quality of service on customer satisfaction with the correlation test results of 0.801. The results showed that service quality was 64.2% of customer satisfaction, the remaining 35.8% was influenced by other factors and the regression equation Y = 13.423 + 0.779X with constants a 13.423 and constant b 0.779 means that there is a positive unidirectional relationship between service quality and customer satisfaction at Waroeng Steak and shake Margonda.